Applicability of methodological strategy in vocational guidance program of secondary-technical education. Venezuela - Cueto, Ruth (2024)
The progress of a qualitative study of exploratory scope is presented, in which the objective was formulated to evaluate the applicability of a methodological strategy for the Vocational Guidance Training Area Program in Secondary-Technical Education of Venezuela, which allows serving students from first to fifth year, with the assistance of at least one counselor in each educational institution. It is proposed to administer a modular, rotating, inter-institutional and multidisciplinary structure. The data was obtained through the use of three analysis resources, the review of legal and institutional documents, the comparison with a similar precedent carried out at the Faculty of Medicine of the University of Zulia during the period 1997-2008 and the assessment of a simulation exercise. Among the conclusions, it stands out that its management requires, on the one hand, strengthening conditions among the Educational Community such as discipline, concentration, patience and concern for the desired objectives and, on the other, the administration of a pilot test during the 2023-2024 school year.